2013
DOI: 10.1186/1472-6939-14-45
|View full text |Cite
|
Sign up to set email alerts
|

How experience makes a difference: practitioners’ views on the use of deferred consent in paediatric and neonatal emergency care trials

Abstract: BackgroundIn 2008 UK legislation was amended to enable the use of deferred consent for paediatric emergency care (EC) trials in recognition of the practical and ethical difficulties of obtaining prospective consent in an emergency situation. However, ambiguity about how to make deferred consent acceptable to parents, children and practitioners remains. In particular, little is known about practitioners’ views and experiences of seeking deferred consent in this setting.MethodsAs part of a wider study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 48 publications
10
66
0
Order By: Relevance
“…CATCH was one of the first UK studies to use deferred consent in children, and ethics committee decisions (Box 1) were based on opinion because there was a lack of evidence about potential biases caused by exclusion of nonconsenting participants. [15][16][17][18] We aimed to inform future decisions on the use of deferred consent in children by evaluating rates of deferred and prospective consent and reasons for nonconsent for emergency and elective admissions in the CATCH trial.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…CATCH was one of the first UK studies to use deferred consent in children, and ethics committee decisions (Box 1) were based on opinion because there was a lack of evidence about potential biases caused by exclusion of nonconsenting participants. [15][16][17][18] We aimed to inform future decisions on the use of deferred consent in children by evaluating rates of deferred and prospective consent and reasons for nonconsent for emergency and elective admissions in the CATCH trial.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Ongoing research (the CONNECT study) is investigating more closely the experiences of parents recruited to CATCH and may help explain why deferred consent rates were not even higher. 15 A major concern relating to deferred consent in CATCH is that inclusion of children in analysis was related to the child's outcome. In CATCH, 13% of patients admitted on an emergency basis were not approached for deferred consent, mainly because many were discharged or transferred before the approach could be made.…”
Section: Figurementioning
confidence: 99%
“…Professionals without previous experience of deferred consent have been found to be apprehensive about the approach or find it inappropriate not to give parents any choice before starting the study. 35,39 On the other hand, approximately two-thirds of parents of critically ill children reported that deferred consent was acceptable to them, 41 or parents suggest that professionals should just get on with treating their child and worry about consent later. 39 These different viewpoints indicate the need for further discussion and reflection on the best practice regarding the informed consent process and to consult with parents (and, if feasible, young people) as partners in the design of consent procedures for trials that will be implemented in emergency settings.…”
Section: Iii2 Potential Solutionsmentioning
confidence: 99%
“…38 Although deferred consent helps to avoid this difficulty, clinicians might feel uncomfortable approaching bereaved parents for consent or about conducting study activities such as blood sampling before consent has been sought. 35 …”
Section: Iii1 Trials That Have No Time For Prospective Consentmentioning
confidence: 99%
See 1 more Smart Citation